ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPATUHAN WAJIB PAJAK ORANG PRIBADI KABUPATEN PANIAI (Studi Kasus Pada Kantor Pelayanan Pajak Pratama Kabupaten Timika) - Seri Ma Helena Yeimo; Melinda Malau; Ganda T. Hutapea (Fundamental Management Journal, 2023)
The formulation of the problem in this study is the factors that influence individual taxpayer compliance. The purpose of this research is to find out whether Fiskus services, awareness of paying taxes, and insights about taxes have an impact on compliance with the obligation to invite individuals. The data analysis used was (1) descriptive statistical test, namely determining the maximum value, minimum value and average value (mean) as well as the standard deviation of the data, (2) multicollinearity test, normality and heteroscedasticity, (3) multiple linear regression test, is to use a partial or simultaneous significance test. In this study only used a partial test. The data used is sourced from primary data using questionnaires for individual taxpayers in Paniai Regency as respondents. The results of the first data analysis at a significance value of 0.000 <0.05 means that the size of the tax authorities has an impact on individual taxpayer compliance, the second significance value of 0.393 > 0.05 means awareness of paying taxes has no impact on individual taxpayer compliance, the third significance value is 0.001 <0.05 means that insight into taxes has an impact on individual taxpayer compliance. The conclusion is that tax authorities and tax knowledge have a big influence in carrying out tax obligations, but taxpayers do not have the awareness to carry out their tax obligations. Suggestions for future researchers are expected to enlarge the scope of research, the tax authorities can be more proactive and improve the quality of services and additional facilities that can support the breadth of taxpayers to fulfill their tax obligations. Keywords : Compliance; Fiscal Service; Knowledge; Paying Awareness